Reestructuración técnico administrativa en el hotel Boutique San Rafael, ubicado en San Sebastian de Mariquita Tolima (2020)
The San Rafael boutique hotel is an accommodation services company; These types of hotels are characterized by having personalized customer service, differentiating themselves from other hotels by being more exclusive in their services. The present work is about the realization of a technical administrative restructuring in the Hotel Boutique San Rafael, located in the municipality of Mariquita Tolima. A diagnosis is made where the internal and external factors of the company are evaluated, highlighting the positive and negative aspects, and based on them, make some technical and administrative adjustments that contribute to the integral improvement of the hotel.